Estudio comparativo: parto vaginal vs parto quirúrgico en las pacientes atendidas en el hospital Sagrado Corazón de Jesús, Quevedo-Los Ríos primer semestre 2015. - Arana Martinez, Karen Lissete (2015)
This research was carried out in the Sacred Heart hospital in the city of Quevedo, in the province of Los Rios, in the first half of 2015. Objective: To institutionalize vaginal delivery; thereby breaking myths and beliefs to the contrary, in order to reduce the rate of cesarean delivery promoting humanized. Methods: Deductive-Historical. Types of Research: correlational study, field research. Techniques and instruments: Computer, Camera, reference texts. Results: The research work will through its implementation, development and application will be of great importance because it managed to decrease the rate of operative deliveries, without justification in terms pregnancies without risk factors. Conclusions: it was possible to detect a lack of vaginal deliveries with an increase in the rate of surgical delivery, not fully justified in their medical records.